Validade de conteúdo e processos de respostas de um instrumento de rastreio para disfagia orofaríngea no Acidente Vascular Encefálico - Almeida, Tatiana Magalhães de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The incidence and prevalence of oropharyngeal dysphagia and complications are common after cerebralvascular accidents (stroke) and this symptom can be considered an independent predictor of poor prognosis in this population. It is key to the early identification of this symptom be performed by a valid tool in this population. Therefore, due to the lack of consensus on the international and national level on what should be the appropriate tool, this study aimed to verify the validity evidence based on the content and response processes of the screening tool for oropharyngeal dysphagia in stroke. The first version was developed based on the literature review, divided into two parts. The Phase I with 18 questions related to predictive risk factors for oropharyngeal dysphagia and Step II with 11 questions related to indicative signs of oropharyngeal dysphagia associated with the observation of a meal with a homogeneous pasty diet. A group of 19 judges, speech language pathologists and other from other healthcare areas with expertise in the area of oropharyngeal dysphagia agreed to participate in the study and were asked to assess the content of the tool by checking its clarity and relevance. To determine the acceptance of the questions by the judges, the content validity index (CVI-I) for each item of the tool and the total set of items (CVI-T) was calculated, with accepted values above 0.78. In the assessment from judges eight items of the Step I and four items of the Step II have not reached the CVI baseline. The authors reviewed the items and a second version was produced with 12 items in Step I and 5 items in Step II. To research of validity evidence based response process, 23 professional health administered the tool and answered questions based on a structured scale and a cognitive interview about their understanding of the items and possible issues during administration.The answers revealed misconceptions and doubts by some health...

A incidência e a prevalência de disfagia orofaríngea, bem como as complicações, são frequentes após o Acidente Vascular Encefálico (AVE) e esse sintoma pode ser considerado um preditor independente do mau prognóstico nessa população. É de fundamental relevância que a identificação precoce desse sintoma seja realizada por um instrumento válido nessa população. Portanto, devido à ausência de consenso, em âmbito internacional e nacional, sobre qual deve ser o instrumento adequado, este estudo teve por objetivo verificar a evidência de validade baseada no conteúdo e processos de resposta de um instrumento de rastreio para disfagia orofaríngea no AVE. A primeira versão do instrumento foi elaborada baseada na revisão de literatura, sendo dividido em duas partes. A Etapa I incluiu 18 questões relacionadas a fatores preditivos de risco para disfagia no AVE e a Etapa II com 11 questões relacionadas a sinais indicativos de disfagia associados à observação da alimentação com uma dieta pastosa homogênea. Um grupo de 19 juízes, fonoaudiólogos e de outras áreas da saúde, com expertise na área de disfagia orofaríngea aceitaram participar da pesquisa e foram convidados a avaliar o conteúdo do instrumento verificando sua clareza e pertinência.Para determinar a aceitação das questões pelos juízes foi calculado o índice de validade de conteúdo individual (IVC-I) para cada item do instrumento e o índice de validade de conteúdo total (IVC-T) para o conjunto de itens, sendo aceitos valores acima de 0,78.Na avaliação dos juízes verificou-se que na Etapa I do instrumento oito itens não atingiram o IVC mínimo e na etapa II quatro itens. Os autores revisaram os itens e a segunda versão foi elaborada com 12 itens na etapa I e 5 itens na etapa II.Para a investigação das evidências de validade baseada nos processos de resposta, 23 profissionais da saúde adminstraram o instrumento e responderem questões baseadas em...
Keywords: Acidente vascular cerebral; Disturbios da deglutição; Fonoaudiologia - Avaliação